2020
DOI: 10.3389/fnagi.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gray Matter Atrophy in Behavioral Variant Frontal Temporal Dementia and Amyotrophic Lateral Sclerosis: A Coordinate-Based Meta-Analysis

Abstract: Background: There is growing evidence supporting behavioral variant frontotemporal dementia (bvFTD) and amyotrophic lateral sclerosis (ALS) as extreme points of a disease spectrum. The aim of this study was to delineate the common and different patterns of gray matter atrophy associated with bvFTD and with ALS by pooling together the results of previous voxel-based morphometry (VBM) studies. Methods:We retrieved VBM studies that investigated gray matter atrophy in bvFTD patients vs. controls and in ALS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 89 publications
(107 reference statements)
5
10
0
Order By: Relevance
“…It is noteworthy that while areas of GM atrophy were found in all three groups of patients compared to CTR, WM atrophy was more disease specific, with extensive involvement in FTSD and some involvement in FTSD-ALS. Atrophy of frontal and temporal cortices in FTSD patients confirms previous results (Kanda et al, 2008;Luo et al, 2020), whereas spread reduced WM volumes indicates an overall network disruption that may be independent or secondary to GM atrophy. The present cross-sectional data cannot answer mechanistic questions on WM and GM alterations in FTSD patients, that need to be dealt with appropriate dedicated longitudinal studies where the interplay of GM and WM involvement can be followed over time.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is noteworthy that while areas of GM atrophy were found in all three groups of patients compared to CTR, WM atrophy was more disease specific, with extensive involvement in FTSD and some involvement in FTSD-ALS. Atrophy of frontal and temporal cortices in FTSD patients confirms previous results (Kanda et al, 2008;Luo et al, 2020), whereas spread reduced WM volumes indicates an overall network disruption that may be independent or secondary to GM atrophy. The present cross-sectional data cannot answer mechanistic questions on WM and GM alterations in FTSD patients, that need to be dealt with appropriate dedicated longitudinal studies where the interplay of GM and WM involvement can be followed over time.…”
Section: Discussionsupporting
confidence: 87%
“…In ALS patients, previous studies reported atrophy in non-motor areas involved in executive and behavioral functions, such as frontal, temporal and limbic regions (Menke et al, 2014;Luo et al, 2020). Although our ALS patients did not show atrophy in those regions, the involvement of motor and premotor regions emerging from a less stringent statistical analysis is indeed consistent with motor symptoms onset in ALS.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…[10] A meta-analysis of voxelwise studies in grey matter in DLB found atrophy in the bilateral insula cortex [11] and some studies have also found insula atrophy in prodromal DLB. [12,13] However, insula atrophy has also been identified in AD, [14] fronto-temporal dementia, [15] and associated with cognitive impairment in HIV infected individuals. [16] Since there have been relatively few studies investigating the diagnostic utility of these two structural brain markers in mild cognitive impairment (MCI), the aim of this study was to investigate them in a cohort of probable MCI with Lewy bodies (MCI-LB) compared to MCI with no core features of Lewy body disease (MCI-AD).…”
Section: Introductionmentioning
confidence: 99%
“…The functional cognitive disorder may also occur well before the disease begins if Aβ is produced and cholinergic systems dislocate. Nanoparticles combine the targets, visualization, and treatment in one form to give drug molecules new hope and cross BBB [6]. Figure 1 shows the effects of different types of nanoparticles on the treatment of Alzheimer's.…”
Section: Introductionmentioning
confidence: 99%